Restorative Justice dalam Kasus Anak Pelanggar Lalu Lintas - Utoro, Rio Anggid Bambang; Nadir, Nadir; Pakendek, Adriana (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2025)
his study examines the criminal liability of children involved in traffic violations resulting in injury, viewed through the lens of restorative justice. The involvement of minors in traffic accidents often presents a legal dilemma, as it requires a careful balance between protecting the rights of victims and safeguarding the legal interests of the child offender. The primary objective of this research is to analyze the extent to which restorative justice principles can be applied to child offenders in traffic-related incidents and to identify the obstacles hindering their effective implementation. The research employs a normative juridical approach, drawing upon relevant statutory regulations, legal doctrines, and scholarly literature. The findings reveal a normative disharmony between Law No. 22 of 2009 on Road Traffic and Transportation, which emphasizes a retributive approach, and Law No. 11 of 2012 on the Juvenile Criminal Justice System, which prioritizes restorative justice. In practice, the application of diversion mechanisms and restorative justice in cases where child traffic offenders cause injury remains suboptimal. This is due to limited understanding among law enforcement officials, the absence of clear technical guidelines, and resistance from victims or their families. The study contributes to the academic discourse by recommending regulatory harmonization and capacity building among legal institutions to realize a juvenile justice system that is fair, educational, and restorative in nature.